PERSEPSI PESERTA DIDIK TENTANG PELAKSANAAN TES PSIKOLOGIS DI SMK NEGERI 6 PADANG - Lisa, Mona - (Bimbingan dan Konseling, 2014)
This research is besand on he learners perception about the implementation of psychology test. Based on the observation that held in SMK Negeri 6 Padang in August 2013, there were still learners that were not motivated implementation the psychology test was taking place, while the test was taking place, they did test impulsively, they were not serious, they still didnât comprehand the psychology test result that obtuvied and they saw it to in importance party. The purpose of this research is to discribe 1) the learners perception about the function of psychology test, 2) the learners perception about the purpose of psychology test, 3) the learners perception about the result of psychology test, 4) the learners perception about the progress of psychology test result.the type of this research is quantitative desciptive research with the population of learners class X in SMK Negeri 6 Padang that cinsists of 364 students and the samples are 78 students. The samples are taken by using simple random sampling technique. The tool that used to collect data is questionaire. To describe the data of learners perception about the implementing psychology test by using percentage analysis technique. The result of this research shows that how the learners perception about the function of psychology test is standing on agree category, the result of psychology testis also on agree category and the progress of the test is also standing on agree category. So it can be concluded that the learners perception about the implementing of psychology test in class X SMK Negeri 6 Padang is standing on agree category. This research is recommenden to the learners later they can more comprehend and understand the implementation of psychology test.